Factors Influencing Stigma Toward Individuals Who Have Substance Use Disorders. (7th June 2019) - Witte, Tricia H.; Wright, Amber; Stinson, Elizabeth Ashley
Abstract: Objective: This study investigated whether certain misperceptions of substance use disorders (SUDs) would influence stigmatizing attitudes toward individuals who have SUDs. Method: Using a between-subjects design, 1059 young adults (77.2% women) read vignettes describing characters with high or low levels of the following factors: responsibility, controllability, immorality, willpower, consequences, and accountability. Participants then completed measures of stigma toward each character (i.e., affective reactions, negative judgments, and social distancing). Results: Characters described as having low levels of accountability (i.e., denial), low levels of willpower, and severe consequences for their SUDs elicited higher levels of stigma compared to characters without these qualities. However, experimental manipulations of responsibility for one's SUD, controllability of one's SUD, and level of immorality associated with one's SUDs had no significant effect on stigmatizing attitudes. Conclusions: These findings have important implications for educational programs aimed at reducing public stigma toward SUDs.